Carbon Dioxide Sequestration by Using a Model Carbonic Anhydrase Complex in Tertiary Amine Medium. Issue 23 (13th November 2015) - Sivanesan, Dharmalingam; Choi, Youngju; Lee, Jiyeon; Youn, Min Hye; Park, Ki Tae; Grace, Andrew Nirmala; Kim, Hak‐Joo; Jeong, Soon Kwan
Abstract: Globally, the elevation of carbon dioxide (CO2 ) levels due to the anthropogenic effect poses a serious threat to the ecosystem. Hence, it is important to control and/or mitigate the level of CO2 in the atmosphere, which necessitates novel tools. Herein, it is proposed to improve CO2 sequestration by using model complexes based on the enzyme carbonic anhydrase (CA) in aqueous tertiary amine medium. The effect of substituents on the model CA model complexes on CO2 absorption and desorption was determined by using a stopped‐flow spectrophotometer to follow pH changes through coupling to pH indicator and a continuous stirred‐tank reactor (CSTR). The CO2 hydration rate constants were determined under basic conditions and compound6, which contained a hydrophilic group, showed the highest absorption or hydration levels of CO2 (2.860×10 3 L mol −1 s −1 ). In addition, CSTR results for the absorption and desorption of CO2 suggest that simple model CA complexes could be used in post‐combustion processing. Abstract : Clean surroundings : The effects of the substituents of carbonic anhydrase (CA) models on carbon dioxide (CO2 ) absorption and desorption are reported. The CO2 hydration rate constants are calculated under basic conditions, and compounds with hydrophilic groups show the highest hydration rates of CO2 .